No two persons [large type] - Bauermeister, Erica (Thorndike Press large print dynamic drama, 2023)
"Alice has always wanted to be a writer. Her talent is innate, but her stories remain safe and detached, until a devastating event breaks her heart open, and she creates a stunning debut novel. Her words, in turn, find their way to readers, from a teenager hiding her homelessness, to a free diver pushing himself beyond endurance, an artist furious at the world around her, a bookseller in search of love, a widower rent by grief. Each one is drawn into Alice's novel; each one discovers something different that alters their perspective, and presents new pathways forward for their lives. Together, their stories reveal how books can affect us in the most beautiful and unexpected of ways--and how we are all more closely connected to one another than we might think"--